APLIKASI MICROSOFT TEAMS DALAM MENINGKATKAN KETERAMPILAN MENULIS ESAI - Franscy, Franscy; Hidayati, Dini; Solo, Lenny; Zahari, Musril (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2023)
This research aims to determine the effectiveness of the Microsoft Teams application in teaching essay writing skills to students in class XI SMA Bangun Cipta Rumbia, Lampung. Based on the result of preliminary observation shows that students learning outcome was still low and there were some problems related to the impact of their writing skills that still have not achieved the expected aims. This research used the action research method, involving 30 students. Quantitative data was taken from the results of comparing the results of writing essays on initial conditions (pre-cycle), cycle 1, and cycle 2, while qualitative data was taken during observation and action. The results showed that there was an increase in learning activities and learning outcomes in writing essays for students. This increase is known from the percentage of students' activeness in participating in the learning process has increased, the results obtained in cycle 2 the percentage of